Winter Waterbird Community Composition and Use at Created Wetlands in West Virginia, USA - Hannah L. Clipp; Michael L. Peters; James T. Anderson (Scientifica)
Information on nonbreeding waterbirds using created wetlands in the Central Appalachian region of the United States is limited. We compared waterbird communities of two managed wetlands, created in 2013 and 2001, in West Virginia. We observed 27 species of waterbirds. Species richness and diversity were generally similar between the wetlands, but species composition and use differed. Branta canadensis (Canada Geese), Anas strepera (Gadwall), Bucephala albeola (Buffleheads), Aythya affinis (Lesser Scaup), and Aythya collaris (Ring-Necked Ducks) used the older wetland most frequently. Disparities in species use were the highest in March. The older wetland differed from the younger in supporting species such as diving ducks, possibly due to differences in size, vegetation, water depth, and microtopography. However, the ability to provide habitat for waterbirds during the winter was determined to be comparable between wetlands, despite their age difference.